Host diversity mediates the influence of landscape structure on parasite communities in Cerrado agricultural landscapes - Teles, Wanderson Siqueira; Regolin, André Luis; Andrade‐Silva, Beatriz Elise; Maldonado Junior, Arnaldo; Vilela, Roberto do Val; Borges‐Almeida, Karen; Pereira, Marcio Junior; Araujo, Matheus Lima; Collevatti, Rosane Garcia (Annals of the New York Academy of Sciences, 2025)
Parasites are key elements in ecosystem functioning owing to their role in hosts’ population dynamics and abundance, regulation stabilizing trophic networks, and shaping community structure. Landscape changes can affect parasite communities because of changes in suitable microhabitats and on hosts’ community structure. In the Brazilian Cerrado, no study has so far analyzed the effects of intensive agricultural landscaping on helminth parasites of mammals. Here, we fill this knowledge gap, addressing the effects of landscape structure and the Sigmodontinae host's community structure on the richness and abundance of helminth parasites in agricultural landscapes. Using structural equation models, we found that the parasites’ richness and abundance are determined mainly by the rodent hosts’ community structure and are only indirectly affected by landscape structure. We found no direct effect of habitat fragmentation, habitat amount, and landscape compositional heterogeneity on the richness and abundance of helminth parasites, but they directly affected the hosts’ community. Moreover, we found no difference in both the host's and parasite's richness and abundance between crop growing and fallow seasons. Our results show that efforts to preserve helminth parasites may comprise landscape conservation strategies that preserve the biodiversity of the rodent hosts, including conservation and restoration of vegetation remnants at the landscape level. Here, we address the effects of landscape composition and configuration, as well as the community structure of Sigmodontinae (Cricetidae: Rodentia) rodent hosts, on the richness and abundance of helminth parasites in agricultural landscapes in the Cerrado ecoregion.